Clinical Evaluation of Ridge Preservation Techniques Following Tooth Extraction in Pakistani Patients - Tariq Javed, Qurat Ul Ain, Amna Azam, Muhammad Bilal, Eram Najm, Sohail Fareed, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Alveolar ridge remodeling following tooth extraction often compromises future restorativeoptions, highlighting the need for predictable ridge preservation protocols. This experimental clinical study evaluated two ridge